2018
DOI: 10.1111/aogs.13508
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pain thresholds and signs of sensitization in women with persistent pelvic pain and suspected endometriosis

Abstract: Introduction: Endometriosis is a gynecological disorder that may cause considerable pelvic pain in women of fertile age. Determining pain mechanisms is necessary in order to optimize the treatment of the disease. The objective of the study was to evaluate pain thresholds in women with persistent pelvic pain with and without confirmed endometriosis, and healthy, unaffected controls, and analyze how pain thresholds in these cohorts related to duration of pelvic pain, quality of life, and symptoms of anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 26 publications
3
70
0
Order By: Relevance
“…In our previously published study concerning pain thresholds in women with PPP, we found widespread alterations in pain thresholds in women with PPP that are indicative of central sensitization and a time‐dependent correlation (Grundström et al, ). The present study represents a secondary analysis of the data from that study.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In our previously published study concerning pain thresholds in women with PPP, we found widespread alterations in pain thresholds in women with PPP that are indicative of central sensitization and a time‐dependent correlation (Grundström et al, ). The present study represents a secondary analysis of the data from that study.…”
Section: Introductionmentioning
confidence: 68%
“…The pressure was registered in a protocol and the arithmetic average was calculated and used as the actual pressure pain threshold (Mücke et al, ). Since the differences in pain thresholds between the PPP and controls on all sites were almost similar and symmetric for bilateral sites (Grundström et al, ) and in order to minimize multiple testing, we choose to use a composite measure of pain threshold in the analyses. The mean value for each modality (heat, cold and pressure) was calculated as the average of the pain thresholds on all locations and used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged exposure to pain could trigger a state of central sensitisation, with an altered perception of pain 26 . It was recently shown that women with chronic pelvic pain had a lower pain threshold than healthy controls and that pain threshold decreases with increasing symptom duration 27,28 . This supports the idea that prolonged exposure to pain increases the risk of developing an altered perception to pain, which could be harder to treat with hormonal and surgical means.…”
Section: Discussionmentioning
confidence: 87%
“…The pathophysiology of the pain is unclear. Authors have reported mechanisms of viscero‐somatic referral sensitization 4,5 and central sensitization according to the time‐lapse in which patients complain of their pain 6 . Moreover, chronic pelvic pain is associated with psychological distress, psychiatric disorders, 7 and previous sexual abuse history 8 suggesting psychological involvement in pain perception.…”
Section: Introductionmentioning
confidence: 99%